Adoption and Impact of Crop Diversification in Rice-Based Systems on Farmer’s income, yield, and food security in Mali - Diallo, Aboubacar; Suh, Neville; Dossou-Yovo, E. R (2024)
The AICCRA project, introduced in 2021, aims to enhance climate resilience in Mali through crop diversification strategies. It targeted 4,013 rice farmers (1,657 males and 2,356 females) in vulnerable regions like Sikasso, Segou, and Koulikoro. The project provided capacity-building workshops, field demonstrations, and extension services to promote diversification. The impact of these interventions on farmers' yield, income, and food security was evaluated using a cluster randomized trial design. Results show that rice farmers engaged in off-season crop diversification experienced a 1,953 kg/hectare increase in yield, a 208,322 FCFA increase in income per hectare, and a food consumption score increase of 21 compared to non-adopters. The study also identified farm, household, and institutional factors influencing farmers' decisions to adopt crop diversification. These findings highlight the importance of promoting crop diversification and understanding the key factors driving its adoption to improve farmers' resilience to climate change in Mali.